Five new species of Macrostomus Wiedemann and a checklist of Empididae (s. str.) (Diptera) from Bolivia - Rafael, José Albertino; Marques, Dayse Willkenia Almeida (Zootaxa, 2019)
Ten Bolivian species of Macrostomus Wiedemann were studied. Five species are redescribed based on type specimens described by Bezzi. The species are included in the following species-groups: four in the M. ferrugineus species-group: M. arcucinctus (Bezzi), M. argyrotarsis (Bezzi), M. dolichopterus (Bezzi) and M. grallatrix (Bezzi); three in the M. limbipennis species-group: M. macerrimus (Bezzi), M. montanus sp. nov. and M. rodriguezi sp. nov.; one species in the M. amazonensis species-group: M. falcatus sp. nov.; and two unplaced to species-group: M. trifidus sp. nov. and M. trilineatus sp. nov. A key to the 12 species of Macrostomus found in Bolivia, including M. limbipennis (Bezzi) and M. pictipennis (Bezzi), is presented. Macrostomus argyrotarsis (Bezzi) is also recorded for the first time from Peru. A checklist of 31 described species of Bolivian Empididae s. str. is included. Three empidid species originally described from Mexico that had previously been recorded from Bolivia, are excluded from the Bolivian fauna.